Peranan Total Quality Management Dalam Meningkatkan Kepuasan Konsumen - Asrizal Asrizal; Mukaram Mukaram (Jurnal Riset Bisnis dan Investasi, 2016)
One of the characteristics that the resulting product quality is the emergence of consumer satisfaction. Customer satisfaction will be achieved when the product quality of an organization that is supported by the implementation of Total Quality Management (TQM). The purpose of this study is to determine the level of implementation of TQM at Sekolah Dasar Islam Terpadu Bina Insan Mulia, determine the level of customer satisfaction atSekolah Dasar Islam Terpadu Bina Insan Mulia, as well as to determine whether TQM affects customer satisfaction at Sekolah Dasar Islam Terpadu Bina Insan Mulia. This study used a saturated sample technique by using the entire population of 113 as the study sample. Based on the results of the research level of implementation of TQM at Sekolah Dasar Islam Terpadu Bina Insan Mulia already "good" it is based on the mean value of 4.0613 is in the interval 3.41 to 4.20, which means that the rate of implementation of TQM at Sekolah Dasar Islam Terpadu Bina Insan Mulia is good. the level of customer satisfaction atSekolah Dasar Islam Terpadu Bina Insan Mulia Bekasi is at a level that is "good" it is based on the mean value of 4.1505 is in the interval 3.41 to 4.20, which means that the level of consumer satisfaction atSekolah Dasar Islam Terpadu Bina Insan Mulia is good. From the results obtained regression analysis models regression coefficient is Y = 9.274 + 0.429x which means that if there is no value of TQM variable, the value of variable consumer satisfaction is equal to 9.274 and if there is additional 1 value of TQM variable then customer satisfaction variable will increase by 0.429. Significance value 0,000 lower than the probability value of 0.05 indicates that the TQMvariable significantly influence customer satisfaction variable. Rated R-square of 0.689 or 68.9% means that the contribution of TQM variable to customer satisfaction variable is at 68.9% while the remaining 31.1% is contributed by other variables outside the study